Resistance economy as a social factor affecting health: a model for evaluating and monitoring the policies of Iranian governmental institutions - Mahdavi , Ehsan; Salajegheh, Sanjar; Pourkiani , Masoud; Sayadi , Saeed; Arabpour, Alireza (Social Determinants of Health, 2022)
Background: The present study aimed to provide an efficient evaluation model in the economic field in the context of resistance economics in Iran. Method: Grounded theory was used as a qualitative method for this study. During the interviews with 10 policy-makers of the policies approved by the Parliament of Iran (representatives of Iran’s parliament in ten periods) and scientific experts, information was collected and the interview data were coded and ultimately provides a pattern of topics and categories and is therefore selected. After conducting the interview, the data obtained through the Document menu of MAXQDA software were entered into the software by selecting the Imported document(s) option, a model was presented by using MAXQDA software, Results: The model has two parts, enablers and results or consequences. Empowerment includes 5 criteria (strategic management, trust in the ability and plans of policymakers, balanced development of inputs and outputs of the science and technology and factors involved in the implementation of policies and infrastructure) and results (perceived, performance and finance). Factors involved in evaluating the resistance to economic policies have included intra-group and institutional collectivism, independence and attention to the views of the Supreme Leader. Conclusion: With the emergence of the nuclear issue in the international arena towards Iran and multilateral sanctions, Iranian economists must try to provide a local model called the resistance economy to get out of the current situation.